Assessment of air quality of Karachi on real-time rainfall data through GIS analysis - Kausar, Anila; Khan, Owais Iqbal; Ejaz, Fizza; Lahori, Altaf Hussain; Ambreen, Romana; Hassan, Mehdi (Ecological Questions, 2025)
Karachi is a metropolitan city lying on the coastline of the Arabian Sea facing the effects of climate change. Weather patterns are changing and in a transition stage as the world is facing weather variability issues, due to climate change. The existing study was performed based on the real-time rainfall in Karachi held on January 29, 30, February 2, 3, and 4th, 2024. January and February are the month of winter in Pakistan and, in the winter, such continuous rainfall spells have never been witnessed by Karachiites for a long time specifically in February rainfall has never been witnessed on such a large scale. Due to such a long dry and cold season, Karachiites used to face health problems related to Air Quality in winter. Such heavy rain changes the environmental conditions in the winter consequently people feel fresh due to clean air. Pollutants i.e., AQI, PM2.5, and SO2 have been monitored on selected days of 36 locations in Karachi. Interpolation techniques have been used in mapping. Results revealed that before the rain, in the air, all observed pollutants existed in large quantities i.e., AQI, PM2.5, and, SO2 ranged from 158.1-310.5, 70.1-260.5 µg/m³, and 113.5-246.9 ppbV respectively declines dramatically i.e., 69.05- 111.9, 48.3-136.8 5 µg/m³, and 50.04-99.9 ppbV after the rain. Results are analyzed through GIS analysis and further tested through Anova statistical analysis. Tree plantation and enhancing green cover can somehow reduce the contamination level of air. Therefore, instead of waiting for rain which does not usually happen in winter. Karachiites should participate in tree plantation activities/green infrastructure to clean the environment and reduce of health issues of Karachiites.